Immunotherapy with epratuzumab in B-cell non-Hodgkin’s lymphoma (Hematology Meeting Reports, 2009)
During the past decade, the anti- CD20 antibody rituximab has become virtually omnipresent in the management of B-cell lymphomas. With ten years of experience comes not only a greater appreciation for the impact that the drug has had on cancer therapy, but also a greater understanding of its limitations. One strategy to improve on the successes of rituximab has been to engineer novel anti-CD20 antibodies. Although these new agents are likely to be at least as effective as rituximab, they face the challenge of proving their superiority. Asecond approach, which has the advantage of producing a drug that might join rituximab rather than supplant it, has been to develop antibodies to novel target antigens.